2022
DOI: 10.1002/ep.13985
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic ion‐imprinted microspheres for the removal of heavy metal ions from aqueous solution

Abstract: Magnetic ion-imprinted microspheres (IIM) with core-shell structure were successfully prepared by reverse emulsion polymerization and applied to adsorb heavy metal ions from sewage. The semi-interpenetrating polymer network composed of cross-linked polyacrylamide (PAM) and linear chitosan (CTS) was used as the microgel shell of microspheres, which can not only fully retain the active sites of CTS but also tightly encapsulate magnetic particle nuclei. In addition, ion imprinting technology was used to further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The adsorption capacity of the core–shell systems decreased when the content of NaCl increased from 0 mol L −1 to 1.00 mol L −1 . Similar behavior was observed by Zhao et al 113 They used different contents of NaNO 3 during the adsorption of heavy metal ions. The adsorption capacity of the microgels decreased with an increase in the content of NaNO 3 from 0 mol L −1 to 0.1 mol L −1 .…”
Section: Adsorption Capacity-enhancing Factors Of Microgelssupporting
confidence: 83%
See 1 more Smart Citation
“…The adsorption capacity of the core–shell systems decreased when the content of NaCl increased from 0 mol L −1 to 1.00 mol L −1 . Similar behavior was observed by Zhao et al 113 They used different contents of NaNO 3 during the adsorption of heavy metal ions. The adsorption capacity of the microgels decreased with an increase in the content of NaNO 3 from 0 mol L −1 to 0.1 mol L −1 .…”
Section: Adsorption Capacity-enhancing Factors Of Microgelssupporting
confidence: 83%
“…This porosity increases the adsorption capacity of the systems. Zhao et al 113 reported the synthesis of a core–shell system, in which the core consisted of Fe 3 O 4 and shell chitosan-poly(acrylamide) CSa-P(AAm) together with Ca 2+ ions. The adsorption quantity of Cr 3+ , Cd 2+ , Pd 2+ , and Cu 2+ ions from water by the synthesized systems was 4.64, 8.20, 18.56, and 37.84 mg g −1 , respectively.…”
Section: Classificationsmentioning
confidence: 99%
“…In addition, the bending vibration peak of NH 2 located at 1604 cm −1 shifted toward the high wave number, indicating the presence of adsorption of the amino group on Cr(III). The shift of this peak was mainly caused by the increase in the bonding constant due to the more uniform distribution of the NH electron cloud density after the nitrogen atom on the amino group shared the lone pair of electrons with Cr(III) 59 . Meanwhile, the OH and NH 2 stretching vibrational peaks at 3600–3100 cm −1 became significantly wider and weaker after the adsorption of Cr(III).…”
Section: Resultsmentioning
confidence: 98%
“…The shift of this peak was mainly caused by the increase in the bonding constant due to the more uniform distribution of the N H electron cloud density after the nitrogen atom on the amino group shared the lone pair of electrons with Cr(III). 59 Meanwhile, the OH and NH 2 stretching vibrational peaks at 3600-3100 cm À1 became significantly wider and weaker after the adsorption of Cr(III). The decrease in electron cloud density of O H and N H functional groups during their coordination with Cr(III) could be explained by the sharing of lone pair electrons between O and N.…”
Section: Adsorption Mechanism Of Gel Microspheresmentioning
confidence: 99%